2021
DOI: 10.3390/w13121643
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis for Road-Bioretention with Three Types of Curb Inlet Using Numerical Model

Abstract: The FullSWOF-ZG (Full Shallow Water Overland Flow with infiltration determined by Zones and Grate-inlet submodules) program was used to simulate the road-bioretention (RB) stripe and evaluate the performance of the RB stripe with three types of curb inlet. The program was revised from the open-source FullSWOF-2D program and the validation results indicated FullSWOF-ZG predicts the RB stripe performance accurately. The model cases of 27 RB with different longitude slopes (S0), cross slopes (Sx), and curb inlet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…On the other hand, the lowest depth of stagnant runoff water was observed in the case of rectangular inlets without any grating (Figure 6). In a computer simulation study conducted by Li et al [13], it was observed that the composite depressed curb inlet was the most efficient to intercept the road runoff, the next best is the local depressed curb inlet, and the undepressed curb inlet was the least efficient. A combination of a curb inlet and grate inlet can intercept almost all of the road surface runoff even for small longitudinal slopes (0.1-0.3%) with a composite depressed curb inlet to reduce water level from the road surfaces.…”
Section: Runoff Depth At the Inletsmentioning
confidence: 99%
“…On the other hand, the lowest depth of stagnant runoff water was observed in the case of rectangular inlets without any grating (Figure 6). In a computer simulation study conducted by Li et al [13], it was observed that the composite depressed curb inlet was the most efficient to intercept the road runoff, the next best is the local depressed curb inlet, and the undepressed curb inlet was the least efficient. A combination of a curb inlet and grate inlet can intercept almost all of the road surface runoff even for small longitudinal slopes (0.1-0.3%) with a composite depressed curb inlet to reduce water level from the road surfaces.…”
Section: Runoff Depth At the Inletsmentioning
confidence: 99%